2005
DOI: 10.1111/j.1540-627x.2005.00130.x
|View full text |Cite
|
Sign up to set email alerts
|

Promoting Small and Medium Enterprises with a Clustering Approach: A Policy Experience from Indonesia

Abstract: Small and medium enterprises (SMEs) 1 in Indonesia are very important for employment creation and are important sources of economic growth and foreign currencies. It is therefore not a surprise that SMEs receive ample attention in Indonesia. In recent years, particular attention has been paid to development of SME clusters. The main aim of this paper is to review government policies on SMEs with a clustering approach, in Indonesia. The paper argues that in many cases, the development policy has not been so suc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
103
0
22

Year Published

2010
2010
2022
2022

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 135 publications
(126 citation statements)
references
References 18 publications
1
103
0
22
Order By: Relevance
“…Artisan communities exist throughout the world, creating wonderful and often low quality products. Setting up handicraft clusters has been attempted at various times with varying degrees of success by various development agencies [4,24,36].…”
Section: Moving Forward: Connecting Artisans To Global Marketsmentioning
confidence: 99%
“…Artisan communities exist throughout the world, creating wonderful and often low quality products. Setting up handicraft clusters has been attempted at various times with varying degrees of success by various development agencies [4,24,36].…”
Section: Moving Forward: Connecting Artisans To Global Marketsmentioning
confidence: 99%
“…MOLINA-MORALES, 2008;WOLFE;NELLES, 2008). Devido às vantagens que os aglomerados podem trazer, tanto para as empresas como para o desenvolvimento regional, várias políticas públicas vêm sendo desenvolvidas, como, por exemplo, a experiência da Indonésia relatada por Tambunan (2005). No Brasil, também existem diversas iniciativas (AMATO-NETO, 2009).…”
Section: E Jonker E Karapetrovic (2004)unclassified
“…The results of studies (Mohd Shariff et al, 2010;Mohd Shariff & Peou, 2008;Nguyen et al, 2009;Sobri Minai & Lucky, 2011) also indicate that in the absence of sturdy market forces in these countries transitional economy, the government must play a decisive role to create those conditions. In addition, the previous studies underlined that government policies have an impact on SMEs activities, linkages and networking in order to cooperation and utilizing resources (Brimble, Oldfield, & Monsakul, 2002;Harvie, 2001Harvie, , 2002Tambunan, 2005). Theoretical and empirical studies (Opara, 2010;Mohd Shariff & Peou, 2008) have shown government policy that seems to be more consistent in influencing the financial performance of the SMEs.…”
Section: Government Policymentioning
confidence: 99%